(untitled) (Global Journal of Human-Social Science, 2012)
This study surveyed the sources availability and use of information for sustainability of petty trade in Ikenne Local Government Area Ogun State Nigeria Observation had shown that petty trade in rural areas of Nigeria has not been given attention as to their growth and sustainability which is achievable through the availability and use of information at their disposal Descriptive survey method was adopted for the study The population was estimated to be about 500 petty traders at Ikenne Local Government Area Sample size was 300 which are 60 of the estimated population Stratified random sampling technique was use in selecting the sample size Structured questionnaire was the instrument used in collecting data Out of 300 copies of the questionnaire distributed to the respondents 280 93 3 were duly completed and returned Descriptive statistics involving frequency count and percentages was employed to analyze data The study established that petty traders lack access to proper and adequate information as information sources available utilized and preferred by the petty traders were market association information minutes of various meetings and radio